UPSUS PAJALE DALAM MENUNJANG PROGRAM SWASEMBADA PANGAN DI KABUPATEN BOLAANG MONGONDOW - Jeremy ., Ponto; Noortje M. Benu; Ribka M. Kumaat (Sam Ratulangi University, 2017)
This study aims to determine the trend of agricultural production in supporting food self-sufficiency program